Grammatical Errors Made by Students in Writing English Descriptive Paragraph: A Study at English Department at Institut Agama Islam Negeri (IAIN) Kerinci - Y. Sonafist; Aridem Vintoni (ELITE JOURNAL, 2019)
This study aimed at describing the types of grammatical errors made by the in writing English descriptive text. The participants of the study consisted of 47 students of English department at Institut Agama Islam Negeri (IAIN) Kerinci. The data were collected from the students’ compositions. The data were analyzed by using Error Analysis (EA). The grammatical errors in the students’ compositions were identified and classified. Each grammatical error was counted and calculated into percentage for frequency. The results revealed that the grammatical errors made by the students fell into seven categories: errors in using verb tense, singular and plural form, articles, prepositions, pronouns, word order (disordering/inversion of subject and verb) and word choice. The number of the errors in each type was apparently different. The most dominant errors were the errors in the use of preposition. There were 23 errors related to the use of preposition (33.3 % of the total errors). Compared to the total errors made by the students, there was only 1 error (1.4 %) in the use of pronouns